2022
DOI: 10.55643/fcaptp.5.46.2022.3891
|View full text |Cite
|
Sign up to set email alerts
|

Food Security of Ukraine: Estimation of Factors’ Impact, Postwar Trends and Ways to Supply

Abstract: The study aimed to determine Ukraine's food security level, and develop the main directions for its increase. To realize the research purpose several tasks were conducted. Firstly, to calculate Ukraine's Food Security Index and compare it with the average World and average European Food Security Index. Secondly, make a forecast of Ukraine's Food Security Index for the next 5 years, and assess its trends. Thirdly, to establish the main factors that have an impact on Ukraine's Food Security Index. Fourthly, to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 19 publications
0
2
0
2
Order By: Relevance
“…Основна мета -забезпечити узгодженість та надійність, дозволяючи споживачам бути впевненими в тому, що продукти працюватимуть так, як очікується. З іншого боку, сертифікація -це процес, з якого незалежний орган перевіряє відповідність продукту встановленим стандартам [1][2][3]. Це не тільки переконує споживачів у якості та безпеки продукції, але також підвищує авторитет компанії та конкурентоспроможність на ринку.…”
Section: Been Identified That Digital Technologies Have Significantly...unclassified
“…Основна мета -забезпечити узгодженість та надійність, дозволяючи споживачам бути впевненими в тому, що продукти працюватимуть так, як очікується. З іншого боку, сертифікація -це процес, з якого незалежний орган перевіряє відповідність продукту встановленим стандартам [1][2][3]. Це не тільки переконує споживачів у якості та безпеки продукції, але також підвищує авторитет компанії та конкурентоспроможність на ринку.…”
Section: Been Identified That Digital Technologies Have Significantly...unclassified
“…Among the Ukrainians, we can single out Kovalova O., Vytvytska O., Rybchinsky R., Kupchenko A., and Tkachenko S., who, as part of their scientific research, developed scientific and methodological provisions and practical proposals for improving food safety monitoring indicators for the purpose of prompt management decisions [1]. Lagodienko V., Franchuk V., Dzyurakh Yu., Melnyk S., Shuprudko N., and Gobela V. determined the general level of food security in Ukraine and proposed the main directions for its improvement [2].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Hobela et al (2022) indicated how the war changed the conditions for forecasting trends in the livestock market. Lagodiienko et al (2022) investigated possible changes in market trends in the postwar period. The peculiarities of food security monitoring during martial law are also indicated in an article by Kovalova et al (2023).…”
Section: Literature Reviewmentioning
confidence: 99%